History of Mahakala Cult in Buryatia - S. R. Batomunkueva (Научный диалог, 2021)
The history of the cult of Mahakala in Buryat Buddhism is considered. A short introduction to the history of the deity is presented. It is noted that this is one of the main patrons of the Geluk school, whose views and traditions have spread among the Buryats. A review of works containing the earliest information on the veneration of a deity in Buryat temples is carried out. It is reported that the cult of Mahakala in Buryatia is represented by the predominant veneration of its three forms: Six-armed, Four-faced and White Six-armed. The important role of the cult of Mahakala, which replaced the most revered shaman spirits-ongons in the common Mongolian world, is shown. It is reported that during the spread of Buddhism among the Buryats, the Sakyas direction with its main patron Gurgon Mahakala dominated among the Mongols. It is noted that, despite the Mongolian traditions, another — the Six-armed form of the deity — was established in Buryat Buddhism. The author believes that this is connected with the name of the first Pandito Khambo Lama Damba-Darzha Zayayev, who introduced veneration of this deity to Buryat Buddhism directly from Tibet and appointed him the patron of the first Buryat Buddhist temple. The conclusion is made about the significance of the Mahakala cult, which not only acquired great importance within the framework of its original religion, but also entered the system of shamanistic beliefs.